Infrared light interaction with impurity gels in superfluid helium - Izotov, A.N.; Efimov, V.B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The quick cooling of impurity–helium mixture into superfluid helium formats a distinctive soft matter — impurity–helium gel, clusters of which conglutinate into nanoparticles. The sizes of the particles and its mutual interaction depend on the nature of impurity atoms and impurity–helium coupling. In the paper we describe an experimental setup and preliminary results of experimental investigation of infrared absorption by water–heliumgel. The comparison of the infrared spectra of gel absorption with water and ice indicates on some peculiarity ofinteraction in water molecules in water–helium gel.